2021
DOI: 10.3389/fpls.2021.695867
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Exogenous Methods to Induce Plant-Resistance Against a Bark-Feeding Insect

Abstract: Exogenous application of the plant hormone methyl jasmonate (MeJA) can trigger induced plant defenses against herbivores, and has been shown to provide protection against insect herbivory in conifer seedlings. Other methods, such as mechanical damage to seedlings, can also induce plant defenses, yet few have been compared to MeJA and most studies lack subsequent herbivory feeding tests. We conducted two lab experiments to: (1) compare the efficacy of MeJA to mechanical damage treatments that could also induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…For each plant type, half of the total number of plants were treated with 10 mM methyl jasmonate (MeJA). This concentration of MeJA has been used in our previous studies ( Chen et al., 2021 ), and shown to effectively increase resistance against the pine weevil in conifer seedlings of similar sizes (height/diameter) as those in the present study. First, MeJA (95%, Sigma-Aldrich, ref.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…For each plant type, half of the total number of plants were treated with 10 mM methyl jasmonate (MeJA). This concentration of MeJA has been used in our previous studies ( Chen et al., 2021 ), and shown to effectively increase resistance against the pine weevil in conifer seedlings of similar sizes (height/diameter) as those in the present study. First, MeJA (95%, Sigma-Aldrich, ref.…”
Section: Methodsmentioning
confidence: 80%
“…The lab set-up, with plants enclosed in large plastic cylinders, may interfere with their usual feeding behavior and thus affect levels of stem area consumed. For instance, Chen et al (2021) found that MeJA was not as effective at reducing pine weevil damage to seedlings in a non-choice 48-hour lab experiment, compared to an earlier field experiment in which MeJA significantly decreased damage (Chen Y. et al, 2020). Moreover, plants were exposed to pine weevils for a short time in the lab compared to the field experiment.…”
Section: Effects Of Se and Meja On Plant Resistance In The Labmentioning
confidence: 96%
“…Nevertheless, some elicitors can be exogenously applied to enhance plant resistance and maintain a balance between quality and resistance. For example, plant defense hormones, including salicylic acid (SA) and jasmonic acid (JA), can be exogenously applied to activate defense responses to enhance plant resistance [ 6 , 7 ]. Hence, the exogenous application of phytohormones may be a feasible solution to balance the trade-off between yield, quality, and disease resistance of crops.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been a lack of research on how to alleviate the decrease in plant resistance, therefore achieving a balance between resistance and quality. Although JA and SA can be exogenously applied to activate defense responses to enhance plant resistance [ 6 , 7 ], there is no report that exogenous JA can balance the trade-off between seed quality and resistance in rice, and the effect of JA on rice blast disease differs depending on the method or timing of JA treatment [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%